In and Ga Codoped ZnO Film as a Front Electrode for Thin Film Silicon Solar Cells - Duy Phong Pham; Huu Truong Nguyen; Bach Thang Phan; Thi My Dung Cao; Van Dung Hoang; Vinh Ai Dao; Junsin Yi; Cao Vinh Tran (Advances in Condensed Matter Physics)
Doped ZnO thin films have attracted much attention in the research community as front-contact transparent conducting electrodes in thin film silicon solar cells. The prerequisite in both low resistivity and high transmittance in visible and near-infrared region for hydrogenated microcrystalline or amorphous/microcrystalline tandem thin film silicon solar cells has promoted further improvements of this material. In this work, we propose the combination of major Ga and minor In impurities codoped in ZnO film (IGZO) to improve the film optoelectronic properties. A wide range of Ga and In contents in sputtering targets was explored to find optimum optical and electrical properties of deposited films. The results show that an appropriate combination of In and Ga atoms in ZnO material, followed by in-air thermal annealing process, can enhance the crystallization, conductivity, and transmittance of IGZO thin films, which can be well used as front-contact electrodes in thin film silicon solar cells.